2022
DOI: 10.1182/blood.2022016747
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of second-line axicabtagene ciloleucel in relapsed refractory diffuse large B-cell lymphoma

Abstract: The ZUMA-7 study demonstrated that Axicabtagene ciloleucel (axi-cel) improved event-free survival (EFS) compared to standard of care (SOC) salvage chemoimmunotherapy followed by autologous stem cell transplant in primary refractory/early relapsed diffuse large B-cell lymphoma (DLBCL) leading to its recent FDA approval in this setting. We modeled a hypothetical cohort of US adults (mean age, 65 years) with primary refractory/early relapsed DLBCL by developing a Markov model (lifetime horizon) to model the cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Similarly, Kambhampati and colleagues concluded that second-line axicabtagene ciloleucel is cost-effective, with an ICER of $93 547 per QALY. The study by Perales et al did not account for progression-related costs associated with CAR T cell crossover, while the study by Kambhampati et al modeled these outcomes based on the ZUMA-1 study. Our findings aligned with these results, although the standard parametric modeling approach that we used yields fewer mean survival gains than the mixture cure modeling approach and is considered more conservative …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Kambhampati and colleagues concluded that second-line axicabtagene ciloleucel is cost-effective, with an ICER of $93 547 per QALY. The study by Perales et al did not account for progression-related costs associated with CAR T cell crossover, while the study by Kambhampati et al modeled these outcomes based on the ZUMA-1 study. Our findings aligned with these results, although the standard parametric modeling approach that we used yields fewer mean survival gains than the mixture cure modeling approach and is considered more conservative …”
Section: Discussionmentioning
confidence: 97%
“…In 2022, two other reports have been published suggesting that second-line axicabtagene ciloleucel would be cost-effective from US health care sector perspective. 40,41 Perales and colleagues 41 used a mixture of cure models to extrapolate survival outcomes from axicabtagene ciloleucel as reported in ZUMA-7 and concluded that second-line axicabtagene ciloleucel is a costeffective treatment, with an ICER of $66 381 per QALY. Similarly, Kambhampati and colleagues 40 concluded that second-line axicabtagene ciloleucel is cost-effective, with an ICER of $93 547 per QALY.…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have highlighted that novel therapies with high up-front costs in hematologic malignancies, such as CAR T-cell therapy in B-cell lymphomas, can be cost-effective, it is important to highlight that most of the targeted agents recently approved for AML are not curative. 40 Finally, a key consideration when interpreting costeffectiveness analyses is whether such analyses were funded by the pharmaceutical industry or were conducted independently or by public agencies, such as the National Institute for Health and Care Excellence (NICE) in the United Kingdom. 41,42 In the following case studies, we use recent cost-effectiveness analyses of liposomal cytarabine/daunorubicin (CPX-351) and azacitidine/venetoclax to highlight how different assumptions of effectiveness, costs, and healthcare resource utilization lead to substantially different conclusions (Table 2).…”
Section: Aml Care Costs Historic Perspective and Limitations Of Cost-...mentioning
confidence: 99%
“…However, in contrast to other hematologic malignancies, such as multiple myeloma, chronic lymphocytic leukemia, or lymphoma, such studies are not available in AML, which limits (or even precludes) cost-effectiveness analyses seeking to evaluate an optimal therapeutic sequence. 40,65,66 Because the conduct of costeffectiveness analyses in these different scenarios is unlikely due to the absence of clinical trial data informing the model inputs, conclusions regarding the cost-effectiveness of a given treatment strategy should clearly not be overinterpreted and may not apply to other subsets of patients.…”
Section: Future Directionsmentioning
confidence: 99%